2016
DOI: 10.1117/12.2219194
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Nyquist signal-reconstruction-free operational modal analysis and damage detection in the presence of noise

Abstract: Motivated by a need to reduce energy consumption in wireless sensors for vibration-based structural health monitoring (SHM) associated with data acquisition and transmission, this paper puts forth a novel approach for undertaking operational modal analysis (OMA) and damage localization relying on compressed vibrations measurements sampled at rates well below the Nyquist rate. Specifically, non-uniform deterministic sub-Nyquist multi-coset sampling of response acceleration signals in white noise excited linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…As shown in Table 4, by increasing the noise level, the values of the natural frequencies identified using FDD method do not change. The results corroborate with those reported by Gkoktsi et al [31]. In the frequency domain methods such as FDD, the natural frequency of a structure is estimated from the peak values of PSD diagram.…”
Section: Natural Frequenciessupporting
confidence: 90%
“…As shown in Table 4, by increasing the noise level, the values of the natural frequencies identified using FDD method do not change. The results corroborate with those reported by Gkoktsi et al [31]. In the frequency domain methods such as FDD, the natural frequency of a structure is estimated from the peak values of PSD diagram.…”
Section: Natural Frequenciessupporting
confidence: 90%
“…The solution of Eq. (7) relies on the weighted least square criterion (7) is treated by the FDD algorithm to extract mode shapes and natural frequencies 14 .…”
Section: Power Spectrum Blind Sampling (Psbs)-based Approachmentioning
confidence: 99%
“…In fact, one may note that even the consideration of 14 M  channels may be unrealistic in practice. However, this is a setting that has been used before in pertinent theoretical studies 14,30,32 , while recent advancements in the hardware implementation of multi-coset samplers provide CRs independently of the number of interleaved ADCs 37 .…”
Section: Mode Shapes Estimation Of the Bärenbohlstrasse Bridgementioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the PSBS approach does not return the time-histories of acceleration response signals but, on the positive side, it is purely signal agnostic in terms of signal structure in the frequency domain and, therefore, indifferent to signal sparsity attributes and/or to additive noise. In this regard, it was shown that the PSBS approach achieves quality mode shape extraction and robust modal strain-based damage detection from response acceleration measurements corrupted by additive noise (Gkoktsi et al, 2016) at rates as low as 80% below Nyquist leading to significant energy consumption gains in wireless sensors (Gkoktsi and Giaralis, 2019).…”
Section: Introductionmentioning
confidence: 99%